2011
DOI: 10.4067/s0718-221x2011000300008
|View full text |Cite
|
Sign up to set email alerts
|

A correlation between the gas and liquid permeabilities of beech wood heat-treated in hot water and steam mediums

Abstract: Heat-treatment, a major method of wood modification for improving dimensional stability and natural durability, has been studied considerably in the scientific literature. This study will focus on the effect of heat-treatment on permeability, an important physical property of wood by subjecting beech samples to two different mediums of hot water and steam, as well as in two buffered hot water of pH 7 and 8. Hydrothermal treatment caused gas permeability to decrease to its lowest value among the treatments (91.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…The mean value of specific longitudinal gas permeability of all specimens was measured to be 6.48 (× 10 −13 m 3 m −1 ) (Figures 2 and 3). Previous studies showed that variability of permeability is very high in solid wood species [8,9,17,18]. In some cases, difference in permeability of two specimens from the same tree, and even the same board or log, would be as high as five times.…”
Section: Resultsmentioning
confidence: 99%
“…The mean value of specific longitudinal gas permeability of all specimens was measured to be 6.48 (× 10 −13 m 3 m −1 ) (Figures 2 and 3). Previous studies showed that variability of permeability is very high in solid wood species [8,9,17,18]. In some cases, difference in permeability of two specimens from the same tree, and even the same board or log, would be as high as five times.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, pH of the treated medium using the buffered solutions is kept constant at a certain level of pH and also the degradation effect of the released acids can be controled in the process of hydrothermal (Talaei 2010). Consequently, the heat treatment in buffered mediums decreases the thermally induced degradation in the wood (Talaei et al 2012a,b;Talaei et al 2011;Taghiyari et al 2011). On the contrary, in the conditions with no buffering medium (tap water), the acidity will highly increase as observed in water condition with a pH of 3.49.…”
Section: Physical Properties Of the Opw Samplesmentioning
confidence: 98%
“…In addition, the acidic buffer solution increase crystallinity index and higher rate of lignin. Meanwhile, the alkaline buffer considerably controls the carbohydrate degradation in the buffered treatment (Talaei et al 2012a,b;Talaei et al 2010Talaei et al , 2011Taghiyari et al 2011). Therefore, the buffer solutions can neutralize and control the the acidity of the medium.…”
Section: Variation Of Ph After Hydrothermal Treatmentsmentioning
confidence: 99%
“…Since the pH value of water medium changes during hydrothermal treatment, buffered hot water (pH 7 and 8) were used to keep pH of the medium constant over the period of hydrothermal treatment. Buffered hot water with pH equal to 7 comprised 411.75 ml Na2Hpo4.2H2O (0.2 M) + 88.25 ml C6H8O7.H2O; and with pH equal to 8 comprised 483.25 ml Na2Hpo4.2H2O (0.2 M) + 13.75 C6H8O7.H2O ( Figure 5) (Taghiyari et al, 2011).…”
Section: Hot Compressed Water Treatmentmentioning
confidence: 99%
“…Pores were blocked slowing down mass transfer rate. Taghiyari et al (2011) reported that treating beech at 180°C in hot water leads to extra extractives settlement on perforation plates and cell walls, which slows mass transfer rates during drying. In contrast, steam treated samples possess pores and cavities with less blockage, therefore dry faster than the control samples.…”
Section: Drying Time and Moisture Ratiomentioning
confidence: 99%